CTC or CEA: Choosing Reliable Markers for Metastatic Colorectal Cancer - Miftahussurur, Prof. Dr. dr. Muhammad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
-